Improving culture performance and antibody production in CHO cell culture processes by reducing the Warburg effect. Issue 9 (22nd May 2018) - Buchsteiner, Maria; Quek, Lake‐Ee; Gray, Peter; Nielsen, Lars K.
Abstract: Lactate is one of the key waste metabolites of mammalian cell culture. High lactate levels are caused by high aerobic glycolysis, also known as the Warburg effect, and are usually associated with adverse culture performance. Therefore, reducing lactate accumulation has been an ongoing challenge in the cell culture development to improve growth, productivity, and process robustness. The pyruvate dehydrogenase complex (PDC) plays a crucial role for the fate of pyruvate, as it converts pyruvate to acetyl coenzyme A (acetyl‐CoA). The PDC activity can be indirectly increased by inhibiting the PDC inhibitor, pyruvate dehydrogenase kinase, using dichloroacetate (DCA), resulting in less pyruvate being available for lactate formation. Here, Chinese hamster ovary cells were cultivated either with 5 mM DCA or without DCA in various batch and fed‐batch bioreactor processes. In all cultures, DCA increased peak viable cell density (VCD), culture length and final antibody titer. The strongest effect was observed in a fed batch with media and glucose feeding in which peak VCD was increased by more than 50%, culture length was extended by more than 3 days, and the final antibody titer increased by more than twofold. In cultures with DCA, lactate production and glucose consumption during exponential growth were on average reduced by approximately 40% and 35%, respectively. Metabolic flux analysis showed reduced glycolytic fluxes, whereas fluxes in the tricarboxylic acid (TCA) cycle were not affected, suggesting that cultures with DCA use glucose more efficiently. In a proteomics analysis, only few proteins were identified as being differentially expressed, indicating that DCA acts on a posttranslational level. Antibody quality in terms of aggregation, charge variant, and glycosylation pattern was unaffected. Subsequent bioreactor experiments with sodium lactate and sodium chloride feeding indicated that lower osmolality, rather than lower lactate concentration itself, improved culture performance in DCA cultures. In conclusion, the addition of DCA to the cell culture improved culture performance and increased antibody titers without any disadvantages for cell‐specific productivity or antibody quality. Abstract : Addition of a pyruvate dehydrogenase kinase inhibitor, dichloroacetate, to CHO fed batch cultures reduced lactate production and extended culture time by three days. As a result, the antibody titre doubled without affecting product quality. Surprisingly, Buchsteiner and coworkers observed no increase in oxidative phosphorylation to compensate for reduced glycolytic activity.